Infectious canine hepatitis in red foxes (Vulpes vulpes) in the United Kingdom. Issue 1 (11th July 2013) - Thompson, H.; O'Keeffe, A. M.; Lewis, J. C. M.; Stocker, L. R.; Laurenson, M. K.; Philbey, A. W.
Abstract : The pathological findings are described in three cases of infectious canine hepatitis in free‐ranging red foxes (Vulpes vulpes) in England. The foxes died after short periods of clinical illness. Mild jaundice and hepatic congestion were evident grossly. On histopathological examination, intranuclear inclusion bodies were visible in hepatocytes, in association with hepatocyte dissociation and necrosis, as well as in renal glomeruli, renal tubular epithelial cells and vascular endothelial cells. Canine adenovirus type 1 (CAV‐1) was isolated from all three foxes. In a serological study, antibodies to CAV‐1 were detected in tissue fluid extracts taken from 11 of 58 (19 per cent) frozen red fox carcases from England and Scotland.